A note on degree of approximation by matrix means in generalized Hölder metric - Değer, U. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
The aim of the paper is to determine the degree of approximation of functions by matrix means of their Fourier series in a new space of functions introduced by Das, Nath, and Ray. In particular, we extend some results of Leindler and some other results by weakening the monotonicity conditions in results obtained by Singh and Sonker for some classes of numerical sequences introduced by Mohapatra and Szal and present new results by using matrix means.